Feasibility and Sensitivity Analysis of Broiler Chicken Farming with the Partnership Pattern of the “Lumajang Broiler Group” in Lumajang Regency - Fara Abafuri Permata; Imam Mustofa; Sunaryo Hadi Warsito; Mohammad Anam Al Arif; Sri Hidanah; Erma Safitri; Widya Paramita Lokapirnasari; Emy Koestanti Sabdoningrum (Journal of Basic Medical Veterinary, 2026)
This study aimed to evaluate the financial feasibility and sensitivity of the broiler chicken farming business of the “Paguyuban Broiler Lumajang” Livestock Group in Lumajang Regency. The research employed a descriptive observational method using a survey approach, involving 20 farmers who were categorized into two groups based on partnership companies (national and multinational companies). Feasibility analysis was conducted using four key financial indicators: Net Present Value (NPV), Average Rate of Return (ARR), Benefit–Cost Ratio (B/C Ratio), and Payback Period (PP). Sensitivity analysis focused on the impact of changes in feed prices (increases of 5%, 10%, and 15%) and broiler selling prices (decreases of 5%, 10%, and 15%). The results indicated that all groups were financially feasible, with positive NPV values, ARR significantly exceeding prevailing interest rates, PP under five years, and B/C Ratio values above 1. Sensitivity analysis revealed that a decrease in broiler selling prices had a greater impact on profit generation than an increase in feed prices. In conclusion, all groups in the “Paguyuban Broiler Lumajang” were financially viable and showed strong potential for further development. Government support in stabilizing broiler prices and feed costs is essential to ensure business sustainability and farmers’ welfare.